Lồng ghép nội dung giáo dục quyền con người cho sinh viên trong dạy học môn Giáo dục pháp luật: Nghiên cứu tại Trường Cao đẳng Sư phạm Bà Rịa - Vũng Tàu - Hoàng, Thị Minh (Tạp chí Giáo dục, 2025)
Human rights education is an important and necessary requirement to help students fully and deeply understand basic human freedoms, thereby changing their actions, promoting respect, preventing violations and abuses of human rights. This article explores the current situation and proposes solutions for human rights propaganda for students through integrating the content of “Human Rights” education into the subject of Legal Education at Ba Ria - Vung Tau Pedagogical College. The results show that the integration has brought great effectiveness in many aspects, such as: students have correct understanding of human rights as well as their own rights and obligations; students always have a sense of compliance with and implementation of the law, contributing to preventing and stopping violations of human rights laws. Equipping students with awareness of human rights is one of the important goals, aiming to orient their awareness for all actions, helping them to have a way of looking at life and making the right decisions, living with ideals for humanity, for the common cause of the country.